Gallbladder Carcinoma Accompanied by Pancreaticobiliary Maljunction With a Rare Double Common Bile Duct. (18th August 2021) - Muramoto, Yuya; Matsumori, Tomoaki; Uza, Norimitsu
Abstract : : Abstract :